The Concept of Transmedia Storytelling Barista on Instagram Content @_temanduduk - Cunk Erlangga; Aghnia Dian Lestari (CV. Media Digital Publikasi Indonesia, 2026)
The development of the coffee shop industry in Indonesia has encouraged businesses to implement digital communication strategies that can build emotional closeness with customers. Instagram has become an important medium in shaping brand narratives through experience-based storytelling. This study aims to examine the role of baristas as key actors in shaping service experience narratives, analyze storytelling forms through four pillars of Instagram content, and understand consumer responses to service experience-based content on the @_temanduduk Instagram account as a communication strategy to increase customer loyalty. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. The research informants include the owner, baristas, and customers of Coffee Shop @_temanduduk who were selected purposively. The results show that baristas have a dominant role in building narratives through four content pillars, namely products, service, entertainment, and trends. These four pillars form a consistent, authentic storytelling structure that represents the daily service experience. The application of transmedia storytelling principles, such as worldbuilding, continuity, performance, and spreadability, encourages emotional and participatory audience engagement. Furthermore, storytelling based on the barista's service experience is effective in building customer trust and loyalty in the digital space.